16 W single-frequency laser output from an Er:YAG ceramic nonplanar ring oscillator. (7th November 2018) - Zhang, M; Gao, C Q; Gao, M W; Zhang, Y X; Huang, S
Abstract: A high-power 1645 nm monolithic Er:YAG ceramic nonplanar ring oscillator (NPRO) is demonstrated. The maximum 1645 nm single-frequency power is 16.10 W, with a slope efficiency of 56.24% and an optical efficiency of 50.15%. The relative power stability of the Er:YAG ceramic NPRO laser is measured to be 0.33% in 30 min. When the temperature of the Er:YAG ceramic changed, the widest continuous tuning range without mode-hoping is 4.21 GHz. The line width of the Er:YAG ceramic NPRO laser is 4.4 kHz. The M 2 factors are 1.20 and 1.27 in x and y directions, respectively.